The Effect of Project-based Learning and Self-Efficacy on Collaboration Skills in Higher Education within a Mobile LMS Environment - Syamsudin, Agus; ., Mustaji; Mariono, Andi; Khotimah, Khusnul (Journal of Ecohumanism, 2025)
This study examines the impact of project-based learning (PjBL) and self-efficacy on collaboration skills among higher education students, utilizing a mobile Learning Management System (LMS). With the increasing integration of mobile technologies in educational settings, this research highlights how mobile LMS platforms can enhance collaborative learning experiences. This study aimed to determine the effect of PjBL and self-efficacy on improving collaboration skills and interaction on the collaboration skills of high school students. This study used a pretest-postest control group design. The number of research subjects was 68 students. The data collection techniques used were questionnaires, observations, and tests. Questionnaires are used to determine the results of student self-efficacy, observations are used to determine student collaboration skills, and tests are used to determine student learning outcomes. The data analysis technique is Manova (multivariate analysis of variance). The result of this study is that project-based learning and self-efficacy have a significant effect on collaboration skills. The results of the Manova test calculation (multivariate analysis of variance) Sig value of the learning model variable and Self Efficacy on collaboration skills is 0.003 significance <0.05 (0.003 <0.05), so it can be concluded that there is an interaction between project-based learning and self-efficacy on collaboration skills